A Light-Weight Fault Injection Approach to Test Automated Production System PLC Software in Industrial Practice. (January 2017) - Rösch, Susanne; Vogel-Heuser, Birgit
Abstract: A light-weight software-implemented fault injection (SWIFI) testing approach is introduced, focusing on technical process faults and system faults. The reaction of automated production systems (aPSs) and their programmable logic controller (PLC) software to these faults is tested. In order to tailor the testing approach to the aPS domain in industrial practice, our test generation is based on a classification of possible deviations, i.e. a classification of possible technical process and system faults as the PLC perceives them. As a result, both specification and test execution become more efficient for practitioners. Furthermore, the test specification is tailored for execution on IEC 61131-3 programming environments. In this, the execution of test cases both against simulation or the real aPS, is enabled. Abstract : Highlights: A test specification and fault classification enabling for the first time software-implemented fault injection testing of error handling routines within the automated production systems (aPS) domain in practice, targeting up to 90% of today's control code, which is made up of error handling. A light-weight specification for testing IEC 61131-3 aPS software error handling. A comprehensive classification of aPS's technical process faults. A generally applicable test case template specification for testing the reaction of aPSs to technical process faults. An approach for automatically generating IEC 61131-3 compliant test cases. The results of applying the entire concept to an industrial case study from a leading aPS manufacturer as well as to a lab-size case study especially regarding execution on PLCs. Quality assurance improvement in the aPS domain assessed together with experts representing German machine and plant automation companies, who are export world leaders.